2016
DOI: 10.3892/br.2016.655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertension on bacteria composition of prostate biopsy in patients with benign prostatic hyperplasia and prostate cancer in PSA grey-zone

Abstract: Abstract. Diagnostic prostate cancer (PC) is difficult to diagnose by prostate biopsy, even in patients with markedly elevated PSA levels. Therefore, we aimed to identify a new, better technique to detect PC in a more consistent manner. A variety of steps were employed to validate this proposed method, including DNA extraction, polymerase chain reaction (PCR) amplification, denaturing gradient gel electrophoresis (DGGE) and DGGE band sequencing. Four transperineal prostate biopsy specimens were obtained from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Inflammation is attributed to the presence of specific biomarkers such as elevated interleukin (IL)-6, tumor necrosis factor alpha (TNFα) and the acute phase protein, C reactive protein (Mechergui et al, 2009 ; Menschikowski et al, 2013 ; Yu et al, 2015 ). Recent work on urological fluids (i.e., urine, seminal fluid, prostatic secretions) as well as prostate biopsies suggests a significant conditional shift toward certain microbial species which may be used as a diagnostic index (Yu et al, 2015 ; Ni et al, 2016 ).…”
Section: Benign Prostate Hyperplasia (Bph) and Prostate Cancermentioning
confidence: 99%
“…Inflammation is attributed to the presence of specific biomarkers such as elevated interleukin (IL)-6, tumor necrosis factor alpha (TNFα) and the acute phase protein, C reactive protein (Mechergui et al, 2009 ; Menschikowski et al, 2013 ; Yu et al, 2015 ). Recent work on urological fluids (i.e., urine, seminal fluid, prostatic secretions) as well as prostate biopsies suggests a significant conditional shift toward certain microbial species which may be used as a diagnostic index (Yu et al, 2015 ; Ni et al, 2016 ).…”
Section: Benign Prostate Hyperplasia (Bph) and Prostate Cancermentioning
confidence: 99%
“…The sequencing results showed that HA-treated tumor was rich in Lachnospiraceae and Lactobacillus sp. Previous studies showed that the microbial population in EPS, urine, seminal fluid, and prostate biopsy in PCa patients were significantly different, indicating correlation between PCa and BPH with microbiota [38]. Several studies had reported that lactobacilli enhance natural killer cell (NK) activity to effectively attack malignant tumor cells in vitro and in vivo [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies on the effect of Lactobacillus on prostate cancer. Intestinal flora is related to human health and immunity, but whether there is any connection between urinary tract infection and intestinal flora—since urinary tract infection will change bacterial flora, which we had reported before [37,38]—had not been investigated previously. Whether Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%